Influence of increasing soil characteristics at the base of reconstructed buildings on their settlement during the construction of the underground part - N. S. Nikiforova; N. S. Semenov (Vestnik MGSU)
Introduction. With the time of operation of buildings and structures, soil compaction occurs under the base of their foundations from all the acting loads from the building. The purpose of the research is to study the movements of the building foundations during the construction of the underground part with their possible preventive reinforcement during reconstruction, taking into account changes in the strength and deformation characteristics of soils. The solution of this problem will allow the most detailed consideration of buildings settlement during reconstruction.Materials and methods. A series of numerical calculations in the PLAXIS 2D software package of the interaction of the foundation with the foundation soil during the reconstruction of a building with the development of underground space, including the construction of two or three underground floors, were carried out.Results. The effect of taking into account the improved soil characteristics with regard to the time of building operation on the settlement of existing foundations during reconstruction with the development of underground space is studied. It was revealed that the reinforcement of foundations with soil-cement elements reduces the settlement during reconstruction approximately in two times. The influence of the number of floors of the designed underground car park on the stress-strain state of the soil massif is considered.Conclusions. Numerical studies show that strengthening of soils under the base of existing foundations leads to a decrease in the building settlement during reconstruction with the development of underground space. Reinforcement of the existing foundation with soil-cement elements makes it possible not to exceed the maximum additional settlement of the reconstructed building. A decrease in the settlement of existing foundations with a decrease in the number of storeys of the designed underground part is revealed.